2016
DOI: 10.1589/jpts.28.896
|View full text |Cite
|
Sign up to set email alerts
|

Effects of horizontal- and vertical-vibration exercises using a blade on the balance ability of patient with hemiplegic

Abstract: [Purpose] This study aimed to compare the effects of horizontal-vibration with those of vertical-vibration training on the balance and gait of patients with stroke. [Subjects and Methods] A sample population of 20 subjects was randomly divided into 2 groups: the horizontal-vibration group and the vertical-vibration group. We evaluated the Berg Balance Scale (BBS) score, Timed Up-and-Go (TUG) test results, and 10-meter Walk Test (10MWT) results at 3 times points: before the training, 3 weeks after the training,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…A total of 13 studies (van Nes et al, 2006;Brogårdh et al, 2012;Gu and Hwangbo, 2016;Qianhao et al, 2018;Sade et al, 2020;Xin-xin et al, 2020;Jin-Ming et al, 2021;Kim and Lee, 2021;Xie et al, 2021;Yan et al, 2021;Le et al, 2022;Wei and Cai, 2022;Zhenying et al, 2022) Forest plot of the effects of WBV training on BBS.…”
Section: Berg Balance Scale (Bbs)mentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 13 studies (van Nes et al, 2006;Brogårdh et al, 2012;Gu and Hwangbo, 2016;Qianhao et al, 2018;Sade et al, 2020;Xin-xin et al, 2020;Jin-Ming et al, 2021;Kim and Lee, 2021;Xie et al, 2021;Yan et al, 2021;Le et al, 2022;Wei and Cai, 2022;Zhenying et al, 2022) Forest plot of the effects of WBV training on BBS.…”
Section: Berg Balance Scale (Bbs)mentioning
confidence: 99%
“…A total of 10 studies (Chan et al, 2012;Choi et al, 2016;Gu and Hwangbo, 2016;Sade et al, 2020;Ijaz Ahmed Burq et al, 2021;Jin-Ming et al, 2021;Kim and Lee, 2021;Xie et al, 2021;Chuan et al, 2022;Zhenying et al, 2022)…”
Section: Timed Up-and-go Test (Tugt) (S)mentioning
confidence: 99%
“…In and Song 9 ) showed that the application of vibration exercises in stroke patients improved walking ability. Gu 10 ) demonstrated that vibration in the horizontal and vertical directions using a body blade in stroke patients showed a significant difference between 10MWT and TUGT values. Vibration stimulation helps strengthen the muscles involved in stability by improving one’s sense of innate receptivity with strong sensory stimuli 9 , 11 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Good balance function is crucial for patients to resume walking and freely move their upper limbs[ 10 ]. Improvements in balance ability can effectively prevent patients from falling and reduce their risk of reinjury[ 11 ]. Kerse et al [ 12 ] conducted return visits with patients who had strokes within 6 mo in New Zealand and found that the incidence of falls was 37%, which was twice that in the general elderly population.…”
Section: Discussionmentioning
confidence: 99%